Cysticercal Encephalitis Presenting with a “Starry Sky” Appearance on Neuroimaging - Patil, Tushar B. (J Glob Infect Dis, 2015)
A lady in her early forties was brought to our hospital in an unconscious state with history of generalized tonic-clonic seizures for last 6 h. She had multiple episodes of seizures in last 4 months, but did not receive any treatment. Relatives also gave a history of fever, headache, and vomiting for last 1 week. Her seizures were controlled with intravenous lorazepam and valproate. Clinical examination revealed a delirious patient with bilateral papilledema, brisk deep tendon reflexes, and extensor plantars. She had aspirated and had bilateral coarse crepitations on chest auscultation. Computed tomography (CT) of brain showed multiple small hyperdense calcific lesions extending throughout both the cerebral hemispheres leading to a “starry sky” appearance, suggestive of cysticercal encephalitis. The patient succumbed to progressive aspiration pneumonitis on the 6(th) day after hospitalization.